Could Plasma CXCL12 Predict Ventricular Dysfunction in Patients with Severe Myocardial Infarction? - Murad, Hussam A. S.; Bakarman, Marwan A. (International Journal of Angiology, 2022)
Plasma level of chemokine CXCL12 can predict adverse cardiovascular outcomes in patients with coronary artery disease, but data on its relationship with severity of coronary stenosis in cases of severe myocardial infarction (MI) are scarce and conflicting. The objective of this study was to investigate link between plasma CXCL12 levels and different grades of left ventricular ejection fraction (LVEF) in statin-treated and -untreated patients with severe MI. A total of 198 consecutive patients with first-time severe MI (ST-elevated myocardial infarction [STEMI], n = 121 and non-ST-elevated myocardial infarction [NSTEMI], n = 77) were recruited from Coronary Care Unit, King Abdulaziz University Hospital. They have one to two coronary arteries blocked ≥50%, or three arteries blocked 30 to 49%. Demographic and clinical criteria were collected and plasma CXCL12 level was measured. No correlations were detected between demographic and clinical criteria and CXCL12 level. While troponin peaks and LVEF significantly differed between STEMI and NSTEMI patients, CXCL12 level showed nonsignificant changes. Plasma CXCL12 levels decreased significantly in statin-treated patients compared with those untreated. From receiver operating characteristic (ROC) analysis, high CXCL12 levels were associated with no statin therapy. For STEMI and NSTEMI patients, area under the receiver operating characteristic curve for CXCL12 test were 0.685 and 0.820, while sensitivity and specificity values were 75.9 and 54.8%, and 73.1 and 84%, respectively. Plasma CXCL12 levels showed nonsignificant changes with different ranges of LVEF and troponin peaks. In patients with severe MI, irrespective of statin therapy, plasma CXCL12 showed no correlation with different ranges of LVEF suggesting that it cannot predict left ventricular dysfunction in these cases. However, cross-sectional design of this study is a limitation.
Keywords: plasma CXCL12; left ventricular ejection fraction; acute coronary syndrome; statin